Tinjauan Pustaka : Sumber Daya Manusia Dan Pertumbuhan Ekonomi Indonesia - Nurhaedah Nurhaedah; Muhammad Junaid Kamaruddin; Ady Kurnia (Economy Deposit Journal (E-DJ), 2022)
Education is the process of developing human abilities such as manners, morals, and intellectual ability so that humans can apply them in everyday life and attain desired goals and happiness without the assistance of others. The philosophical, social, cultural, psychological, scientific and technological, economic, historical, and religious foundations form the basis of education. The essence of education is the extension of the human capacity to learn, as a result of the learner's own efforts, and eventually as a sequence of historic forms of labor organization. Multicultural education involves the concept that all students, regardless of gender, sexual orientation, social status, or ethnic, racial, or cultural features, should have equal access to education. The dimensions of multicultural education are content integration, knowledge construction processes, reduction reduction, pedagogical equity, and Member School Culture and Social Structure. The implementation of multicultural education in Indonesia is still found some deficiencies